RECONSTRUCTING THE VAT THRESHOLD IN INDONESIA: A LITERATURE REVIEW - Sipayung, Bonarsius; Hamzah, Muhammad Zilal; Arsal, Yon (Scientium Law Review (SLR), 2023)
The high threshold to be confirmed as a taxable entrepreneur in Indonesia, which is the amount of gross turnover and/or gross income in a fiscal year of at least Rp 4.8 billion, has attracted criticism from several quarters, including the World Bank. There are even studies that argue the need to determine the ideal VAT threshold in a country, considering that a high threshold will reduce VAT revenue, while a low threshold will impose high compliance costs on small businesses. Based on a normative legal study, this study reaches two conclusions. First, the provisions governing the current VAT threshold in Indonesia have undergone several changes since the enactment of the 1984 VAT/PPnBM Law, with the latest provision stipulating that the amount of gross turnover and/or gross income in a fiscal year must be at least Rp. 4.8 billion. Second, the legal reconstruction of the VAT threshold in Indonesia needs to be carried out while still harmonising with other VAT policies, such as tariffs and the expansion of the VAT base, and taking into account benchmarking in several countries. It is recommended that there be a change in VAT policy on the threshold by not applying a threshold that is too high, taking into account the principle of neutrality, suggestions from competent world institutions such as the World Bank, and benchmarking with several developed countries that have a good VAT system and the imposition of VAT thresholds is not too high, such as Australia, Malaysia, Singapore, and Switzerland.